FILSAFAT SEBAGAI ILMU KRITIS DAN PERANNYA DALAM KEHIDUPAN MANUSIA - Suranto (Jawa Dwipa, 2024)
Philosophy is the mother of all sciences that directs people to think critically, rooted and deep. In this context the author focuses on the philosophical mindset in human life. Philosophy and science are two words that are related to each other, both substantially and historically because the birth of science cannot be separated from the role of philosophy, on the contrary the development of science strengthens the existence of philosophy. The birth of philosophy in Greece on the minds of the Greeks from the point of view of methodology eventually disappeared and in turn it was ratio that was dominant. With philosophy, the mindset that always depends on God is transformed into a mindset that depends on ratios. Natural events such as eclipses are no longer considered as activities of sleeping Gods, but are natural occurrences caused by the sun, moon and earth being in parallel lines, so that the moon's shadow falls on part of the earth's surface. For this reason, this process requires a basic pattern of thinking and a pattern of thinking based on how science is used as a basis for discussing reality.